Early and Medium Outcomes of On-Pump Beating-Heart versus Off-Pump CABG in Patients with Moderate Left Ventricular Dysfunction - Wang,Weitie (2019)
Abstract Objective: This study aims to compare the early and medium outcomes of on-pump beating-heart (OPBH) coronary artery bypass grafting (CABG) and off-pump CABG (OPCABG) in patients with left ventricular ejection fraction (LVEF) between 30% and 40%. Methods: This is a retrospective study of ischemic heart disease patients with LVEF between 30% and 40% who underwent surgical revascularization from January 2013 to December 2017. Patients were divided into OPBH group (n=44) and OPCABG group (n=68), according to the surgical method. Clinical material with early and medium outcomes were investigated and compared between these groups. Results: The two groups had similar baseline. Two OPBH patients and 3 OPCABG patients died in the hospital, which had no statistical significance (P>0.05). OPBH patients received a greater number of grafts (3.74±0.84) and presented more improved LVEF (45.92±7.11%) than OPCABG patients (3.36±0.80) and (42.81±9.29%), respectively, which had statistical significance (P<0.05). An increased amount of drainage during the first 12 hours was found in the OPBH group (P<0.05). Reoperation for bleeding, duration of mechanic ventilation, and other early outcomes had no statistical significance between the two groups. During the medium-time follow-up, OPBH patients showed significantly lower major adverse cardiovascular events (MACE)-free survival time (P=0.049) than OPCABG patients. Conclusion: The OPBH technique was a safe and an acceptable alternative for surgical revascularization in patients with moderate left ventricular dysfunction which provided better mid-term MACE-free survival compared with OPCABG.